2013
DOI: 10.1002/elps.201200430
|View full text |Cite
|
Sign up to set email alerts
|

Combination of hollow‐fiber liquid‐phase microextraction and capillary electrophoresis for pioglitazone and its main metabolites determination in rat liver microsomal fraction

Abstract: Pioglitazone (PGZ), a thiazolidinedione antidiabetic agent, is reported as a potent and selective activator of peroxisome proliferator-activated receptor γ (PPAR γ). This drug has been widely prescribed for the treatment of Type 2 diabetes mellitus. In this regard, this manuscript presents, for the first time, an alternative electrophoretic method for PGZ and its main metabolites determination in rat liver microsomal fraction. The electrophoretic analyses were performed using an uncoated fused-silica capillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Calixto et al [36] proposed an alternative electrophoretic method for PIO and its main metabolites determination in rat liver microsomal fraction. It was carried out on an uncoated fused-silica capillary (48 cm×50 µm i.d.)…”
Section: Methodsmentioning
confidence: 99%
“…Calixto et al [36] proposed an alternative electrophoretic method for PIO and its main metabolites determination in rat liver microsomal fraction. It was carried out on an uncoated fused-silica capillary (48 cm×50 µm i.d.)…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the preliminary investigation also showed that phosphate buffer recorded better electropherograms, in terms of resolution, migration time, peak shape, peak height, baseline noise, and the electric current produced, than borate and acetate buffers. The literature also reported that the use of phosphate buffer was appropriate for MET [ 31 , 36 ] and PIO [ 34 ], with other analytes, assay methods.…”
Section: Resultsmentioning
confidence: 99%
“…The acidity of the buffer may affect mobility and electroosmosis flow (EOF) by altering the dissociation constant of analyte and Si-OH groups on the capillary [ 37 ]. Based on the pKa values of MET (12.4) [ 38 ] and PIO (5.6) [ 34 ], both compounds are positively charged under acidic conditions and can be analyzed by CZE. Notably, atenolol was chosen as an internal standard (IS) because it has a pKa value of 9.6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…reviewed. 4 Various techniques such as uv-spectrophotometry, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] potentiometry, voltammetry, [27][28] high-performance liquid chromatography, [29][30][31][32][33][34][35][36][37][38][39] ultra-performance liquid chromatography, 40 highperformance thin layer chromatography [41][42][43][44][45][46] and capillary electrophoresis 47 have been reported for the determination of PGH in bulk sampleand tablets.…”
Section: Pioglitazone Hydrochloride (Pgh) Chemically Known As 5-[[4-mentioning
confidence: 99%